Zircon U-Pb age constraints for Tonian-early Cryogenian deposition of metasedimentary rocks from the Schirmacher Oasis, East Antarctica: Implications for correlations across the Mozambique Ocean - Vadlamani, Ravikant; Bühn, Bernhard; Pimentel, Marcio (Polar Science, 2018)
Schirmacher Oasis, central Dronning Maud Land, East Antarctica, a dispersed fragment of the 660-610 Ma East African Orogen (EAO), exposes platformal-facies high-grade metasedimentary rocks. Here we constrain the depositional age of these sedimentary rocks to test models relating to timing of the closure of the Mozambique Ocean, the southern segment of the EAO, since Tonian time. Zircon, a proxy for detritus, was dated by LA-MC-ICPMS (206Pb/238U ages) that includes both magmatic and (older) metamorphic populations, in addition to those formed during the granulite-facies metamorphic events (660-600 Ma and 580-555 Ma) having an age range between 1240 and 500 Ma. In conjunction with field evidence, their depositional time is constrained to the Neoproterozoic (Tonian to early Cryogenian, i.e. 1000 >Tdep >800 Ma and 930 >Tdep>800 Ma) with their provenance likely dominated by metamorphic (orogenic) over magmatic rocks. These metacarbonate and psammitic rocks are correlated with similar rocks from the Montepuetz Complex, Northeastern Mozambique, metacarbonate rocks from the Sør Rondane Mountains and with the Linta Group, Vohibory Domain, Southeastern Madagascar. The coeval deposition of platformal sedimentary protoliths, interpreted as occurrence of multiple Mozambique Oceanic strands, were incorporated into the continental arc crust during collision between the Congo and Azania cratonic blocks forming the EAO. journal article